2014
DOI: 10.1186/1756-6614-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative vitamin D deficiency on postoperative hypocalcemia after thyroid surgery

Abstract: BackgroundTransient post thyroidectomy hypocalcemia occurs in up to 30% of patients. We evaluated the effect of vitamin D deficiency on post thyroidectomy hypocalcaemia.MethodsThis is a prospective study which was conducted from November 2010 to January 2013 and a total of 35 patients were included and data was analyzed regarding the relation between preoperative vitamin D3 levels and occurrence of post- thyroidectomy hypocalcemia. Patients were divided into two groups dependent upon the preoperative serum vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…These findings support previous studies that have identified a correlation between VDD and hypocalcemia. In a prospective study of 35 patients, Tripathi, et al, showed that patients with vitamin D concentrations less than 20 ng/ml were more likely to develop postoperative hypocalcemia (6). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support previous studies that have identified a correlation between VDD and hypocalcemia. In a prospective study of 35 patients, Tripathi, et al, showed that patients with vitamin D concentrations less than 20 ng/ml were more likely to develop postoperative hypocalcemia (6). …”
Section: Discussionmentioning
confidence: 99%
“…The impact of vitamin D deficiency (VDD) on the overall incidence and severity of post-thyroidectomy hypocalcemia remains uncertain, but risk factors for VDD can be readily recognized (4,5). The aim of this study is to investigate whether VDD, as defined by the current guidelines of the Endocrine Society (25-hydroxyvitamin D < 20 ng/ml) is associated with increased postoperative hypocalcemia and prolonged hospital stay after total thyroidectomy (6). …”
Section: Introductionmentioning
confidence: 99%
“…Given its role in calcium physiology, several studies have sought to determine whether vitamin D deficiency is an accurate and significant predictor of postoperative hypocalcemia . In a prospective study, Lee et al reported that preoperative serum 25(OH)D levels were not predictive of hypocalcemia after total thyroidectomy for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The number of parathyroid glands identified or reimplanted at the time of surgery was used as the surrogate for transient parathyroid damage. Previously published studies have shown that the risk of postoperative hypocalcemia increases with the increasing number of parathyroid glands identified intraoperatively when utilizing a capsular dissection technique, presumably from transient damage or devascularization of the glands . Patients were considered “high risk” if 3 or more parathyroid glands were identified intraoperatively, and “low risk” if 0‐2 glands were identified.…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that low normal calcium levels were the result of Vitamin D deficiency, which itself has been shown to be one of the factors associated with post-TT hypocalcemia. [18] The idea central to the inception and implementation of this study was the simplicity of its design and thus its applicability to resource-poor settings where iPTH and 25-hydroxy Vitamin D tests are not routinely available. Although iPTH testing has been shown to stratify patients into high- and low-risk for hypocalcemia and expedite an early discharge after TT,[8910] its role in prevention of hypocalcemia is not clear.…”
Section: Discussionmentioning
confidence: 99%